Dog Eat Dog: Balancing Network Effects and Differentiation in a Digital Platform Merger - Farronato, Chiara; Fong, Jessica; Fradkin, Andrey (Management Science, 2024)
Network effects are often used to justify platform strategies such as acquisitions and subsidies that aggregate users to a single dominant platform. However, when users have heterogeneous preferences, a single platform may not be as effective as multiple platforms from both a strategic perspective and an antitrust perspective. We study the role of network effects and platform differentiation in the context of a merger between the two largest platforms for pet-sitting services. To obtain causal estimates of network effects, we leverage geographic variation in premerger market shares and employ a difference-in-differences approach. Our results reveal that although users of the acquiring platform benefit from the merger thanks to network effects, those of the acquired platform are comparatively worse off because their preferred option is removed. Network effects and differentiation offset each other such that at the market level, users are not substantially better off with a combined platform than with two separate platforms. These findings have strategic and regulatory implications as well as highlight the importance of platform differentiation even in the presence of network effects. This paper was accepted by Alfonso Gambardella, business strategy. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2023.4675 .